Usefulness of NIRS in the neurofeedback treatment for depression based on its pathophysiology - Yamawaki, Shigeto; Yokoyama, Satoshi; Okada, Go; Okamoto, Yasumasa (Transactions of Japanese Society for Medical and Biological Engineering, 2021)
Since the COVID-19 pandemic has further increased depression and suicide, the development of its neuroscience-based therapeutic method is urgently required. In our fMRI studies of depressed patients, we found that the hyperfunction of dorsolateral prefrontal cortex (DLPFC) which related loss of motivation, while hypofunction of posterior cingulate (PCC) which related rumination, and these were improved by antidepressant. Focusing on the antagonistic effect between DLPFC and PCC, we carried out a clinical trial of fMRI neurofeedback (NF) targeting DLPFC. We found its antidepressive effect and suggested a potent non-pharmacological treatment for depression. Next, in order to develop a more practical NF treatment for depression, fNIRS-NF targeting DLPFC was carried out on healthy subjects evaluating by the Beck depression inventory (BDI) and rumination-reflection questionnaire (RRQ) as well as its safety and brain functional change by fMRI. In this session, we will introduce our research and discuss the future prospects of fNIRS.